The Television/Audience Complexities: More than Encoding/Decoding - Muzayin Nazaruddin (Jurnal Komunikasi)
Hall opened the article with a critique to the classical tradition of mass communication research that looked at the communication process in a linear fashion, with a model of sender/message/receiver. This classical tradition was over concentrated on the message exchange level; excessively behavioristic, in the sense of looking at communication event as solely a stimulus and response phenomenon; and forgets the complexity of the structures that exist in the communication process itself. Hall then suggested a new understanding of the communication phenomenon, especially at the level of mass communication, which is later known as the ‘encoding/decoding perspective’, in accordance with the title of Hall’s article itself.